Media Pembelajaran Menurut Perspektif Al-Quran dan Al- Hadist - Oktarina, Mikyal (Serambi Tarbawi, 2024)
The use of media from an Islamic perspective, in the Quran and hadits we find many verses that talk about learning media. In the world of education today, educators are required to be more able to present effective learning media according to the times and needs of students. Using descriptive methods, this article tries to describe the learning media contained in the Quran and Hadits, such as audio, visual media, and other multimedia technology learning media that are developing in this era. It is hoped that from the results of this article, educators will better understand the use of media and learning theories in Islam can produce a truly effective learning process.